Computers Helping People with Special Needs 12th International Conference, ICCHP 2010, Vienna, Austria, July 14-16, 2010. Proceedings - Miesenberger, Klaus; Klaus, Joachim; Zagler, Wolfgang; Karshmer, Arthur; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constiutes the proceedings of the 12th International Conference on Computers Helping People with Special Needs, held in Vienna, Austria, in July 2010.
Design for Adaptive Content Processing -- Digital Access to Documents for People with Print Disabilities -- HCI and Non Classical Interfaces -- HCI: Software Accessibility and Social Interaction -- Entertainment Software Accessibility -- Accessible Tourism -- Smart and Assistive Environments -- Usable Web Accessibility: Editing -- Usable Web Accessibility: Education and Motivation -- Usable Web Accessibility: Evaluation -- eGovernment Accessibility -- Accessibility of Blended and E-Learning for Mature Age and Disabled Students and Staff -- Successful Service Provision -- Standards: A Driver for Accessibility and Usability -- People with Speech Impairment: (3z(BWeak and Silent Speech(3y(B: Tools to Support People with Speech Impairment -- People with Speech Learning and Cognitive Problems: Easy-to-Web.s
Keywords: Computer science; Information systems; Multimedia systems; Computer vision; Education; Computer Science; User Interfaces and Human Computer Interaction; Information Systems Applications (incl.Internet).; Computers and Society; Multimedia Information Systems; Computer Imaging, Vision, Pattern Recognition and Graphics; Computers and Education